Therapeutic effects of topical netrin-4 in a corneal acute inflammatory model - Yun Han; Yi Shao; Ting-Ting Liu; Sang-Ming Li; Wei Li; Zu-Guo Liu (International Journal of Ophthalmology, 2015)
AIM: To evaluate the therapeutic effect of netrin-4 on the early acute phase of inflammation in the alkali-burned eye. METHODS: Eye drops containing netrin-4 or phosphate buffered saline (PBS) were administered to a alkali-burn-induced corneal acute inflammatory model four times daily. The clinical evaluations, including fluorescein staining and inflammatory index, were performed on day 1, 4 and 7 using slit lamp microscopy. Global specimens were collected on day 7 and processed for immunofluorescent staining. The levels of inflammatory mediators in the corneas were determined by real-time polymerase chain reaction (PCR). RESULTS: Exogenous netrin-4 administered on rat ocular surfaces showed more improvements in decreasing fluorescein staining on day 4 and 7, and resolved alkali burn-induced corneal inflammation index on day 7 (P<0.01). The levels of IL-1β, IL-6, intercellular cell adhesion molecule-1 (ICAM-1), vascular cell adhesion molecule-1 (VCAM-1), monocyte chemotactic protein-1 (MCP-1) and macrophage inflammatory protein-1 (MIP-1) in corneas were decreased in netrin-4-treated groups (P<0.05). In addition, netrin-4 significantly reduced the expression of leukocyte common antigen 45 (CD45) in the alkali-burn cornea (P<0.001). CONCLUSION: Topical netrin-4 accelerated wound healing and reduced the inflammation on alkali-burn rat model, suggesting a potential as an anti-inflammatory agent in the clinical to treat the acute inflammation.